THE CHARACTERISTICS OF ENGLISH TERMINOLOGIES IN ACADEMIC, SCIENTIFIC TEXT AND ITS USE - Nida, Faridatun; Cahyani, Aulia Putri; Mubarok, Muhammad Adnin; Riandini, Dini (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
Revolution of language style is affected by technology and the field majored by the author; in this case it refers to university students. The use of English terms in scientific text is predictably affected by their English skills. This research aims to know the characteristics of English technical terms that are used by the students and its usage in academic scientific text. The data is collected from the thesis. The result shows that students properly use the terms in the form of phrases, consisting of two to four words, that are abbreviated and not abbreviated, because of their familiarity with the terms. The terms are used to mention the name of variable, the name of application, the name of object, and the name of theory. In order to maintain the use of Indonesian language, the advisors are expected to suggest the students use its equivalent that are available in Bahasa and use it daily so that it is acceptable and familiar for the students.